Urban habitats and food insecurity - Vaz, Eric (2023)
Vaz, E., Damásio, B., Bação, F., Shaker, R. R., & Penfound, E. (2023). Urban habitats and food insecurity: lessons learned throughout a pandemic. Habitat International, 135, 1-11. [102779]. https://doi.org/10.1016/j.habitatint.2023.102779